CORPORATE GOVERNANCE AND ORGANIZATIONAL PERFORMANCE OF KENYA FOREST SERVICE IN NAIROBI CITY COUNTY - Kibuthu, Rahab; Kimencu, Linda (European Journal of Business and Strategic Management, 2022)
Purpose: The objective was to determine the effect of corporate governance and organizational performance of Kenya forest service in Nairobi City County Methodology: The survey adopted stratified sampling and employed questionnaires to collect data from a sample of 166 managerial level staff working at the Kenya Forest Service (KFS) Headquarters' Office at Karura in Nairobi City County. Descriptive and inferential statistical models were employed to analyze, describe, and infer deduction and conclusion from the research findings. Correlation matrix and regressions models were employed to analyze data collected, and describe the research findings in reference to the variables under examination. Findings: The study findings showed that board composition, board independence, board size and board audit committee have an advantageous and significant influence on the iperformance of an organization. Unique contribution to Theory, Practice and Policy: The study recommends that, qthe qKFS qmanagement should qensure more qboard members are qappointed externally to enhance board efficiency and organization iperformance. Additionally, KFS management should increase the number of board members with non-executive status to increase board independence within the organization. The survey findings established that, small boards are preferable to large boards in influencing organization iperformance positively. The study recommends that, sKFS management should design an effective system to identify its ideal board size to promote iperformance.